First Synthesis, Confirmation of Stereochemistry, and Cytotoxic Activity of Oxyfungiformin. Issue 36 (23rd September 2022) - Rahelivao, Marie Pascaline; Bauer, Ingmar; Lübken, Tilo; Kataeva, Olga; Vehlow, Anne; Cordes, Nils; Knölker, Hans‐Joachim
Abstract: The relative configuration of the marine sesquiterpenoid oxyfungiformin, isolated from the soft coral Capnella fungiformis, was confirmed by synthesis using the natural product guaiol as chiral precursor. The absolute configuration of oxyfungiformin could be assigned by combination of X‐ray diffraction and comparison of the values for the specific optical rotation. Oxyfungiformin and a diastereoisomer showed cytotoxic activity in cells originating from cancers of the lung, breast, and cervix. Abstract : The marine sesquiterpenoid oxyfungiformin was obtained in a concise synthetic sequence starting from the chiral precursor guaiol. The absolute configuration of oxyfungiformin was established by a combination of X‐ray analysis and comparison of the values for specific optical rotation. Oxyfungiformin and a diastereoisomer showed cytotoxic activity in a panel of human cancer cell models.